The CssRS two-component system of Bacillus subtilis contributes to teicoplanin and polymyxin B response - Kachan, Alexandr V; Evtushenkov, Anatoly N (Folia microbiologica, 2025)
CssRS is a two-component system that plays a pivotal role in mediating the secretion stress response in Bacillus subtilis. This system upregulates the synthesis of membrane-bound HtrA family proteases that cope with misfolded proteins that accumulate within the cell envelope as a result of overexpression or heat shock. Recent studies have shown the induction of CssRS-regulated genes in response to cell envelope stress. We investigated the induction of the CssRS-regulated htrA promoter in the presence of different cell wall- and membrane-active substances and observed induction of the CssRS-controlled genes by glycopeptides (vancomycin and teicoplanin), polymyxins B and E, certain β-lactams, and detergents. Teicoplanin was shown to elicit remarkably stronger induction than vancomycin and polymyxin B. Teicoplanin and polymyxin B induced the spxO gene expression in a CssRS-dependent fashion, resulting in increased activity of Spx, a master regulator of disulfide stress in Bacillus subtilis. The CssRS signaling pathway and Spx activity were demonstrated to be involved in Bacillus subtilis resistance to teicoplanin and polymyxin B.
Keywords: bakteriální proteiny; antibakteriální látky; Two-component system; Anti-Bacterial Agents; regulace genové exprese u bakterií; promotorové oblasti (genetika); Polymyxin B; Signal Transduction; teikoplanin; signální transdukce; Bacterial Proteins; Promoter Regions, Genetic; Teicoplanin; Cell envelope stress; polymyxin B; Bacillus subtilis; Gene Expression Regulation, Bacterial; Vancomycin